UNLOCKING HIGHER EDUCATION INTEREST: THE IMPACT OF SOCIOECONOMIC STATUS AND LEARNING MOTIVATION AMONG OFFICE MANAGEMENT STUDENTS - Fasya, Ilman Azmi; Faslah, Roni; Wahono, Puji (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This study aims to analyze the influence of parents’ socio-economic status and learning motivation on students’ interest in continuing their studies to higher education, specifically among students majoring in Office Automation and Governance (OTKP) at Public Vocational High School (SMKN) 14 Jakarta. The research employed a quantitative approach with a proportional random sampling technique. The population consisted of 180 students, and a sample of 119 students was selected using a 5% significance level. Data were collected through a survey and analyzed using multiple regression analysis. The results show that: (1) parents’ socio-economic status has a positive and significant influence on students’ interest in pursuing higher education; (2) learning motivation has a positive and significant influence on students’ interest in pursuing higher education; and (3) parents’ socio-economic status and learning motivation together have a significant influence on students’ interest in pursuing higher education.